2015
DOI: 10.3109/10428194.2015.1105370
|View full text |Cite
|
Sign up to set email alerts
|

Double umbilical cord blood transplant is effective therapy for relapsed or refractory Hodgkin lymphoma

Abstract: A sub-group of patients with Hodgkin Lymphoma (HL) who relapse after autologous stem cell transplant can achieve long-term disease-free-survival after allogeneic stem cell transplant (alloSCT). There is limited information regarding the tolerability and efficacy of double umbilical cord blood transplant (dUCBT) for relapsed/refractory HL. We analyzed 27 consecutive, heavily pre-treated patients receiving dUCBT for relapsed/refractory HL at two centers from 2003-2014. The majority of patients relapsed <6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…In this study patients who received low-dose TBI had better OS and PFS and lower NRM in the multivariate analysis [24]. Thompson et al [26] showed the results of 27 patients with HL undergoing UCBT with RIC and MAC regimens, with a 5-year PFS, RI, and NRM of 31%, 38%, and 26%, respectively. Our results are in line with previous reports, supporting these findings in a more comprehensive and uniform cohort of patients who received UCBT.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In this study patients who received low-dose TBI had better OS and PFS and lower NRM in the multivariate analysis [24]. Thompson et al [26] showed the results of 27 patients with HL undergoing UCBT with RIC and MAC regimens, with a 5-year PFS, RI, and NRM of 31%, 38%, and 26%, respectively. Our results are in line with previous reports, supporting these findings in a more comprehensive and uniform cohort of patients who received UCBT.…”
Section: Discussionmentioning
confidence: 60%
“…This study reports 1 of the largest series of HL patients given UCBT. To date, there are limited studies in this settings, with few patients reported [20,[22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Single center and registry retrospective series are also emerging reporting disease-specific outcomes in patients with acute myelogenous leukemia (AML) 11, 12 , acute lymphoblastic leukemia 13,14 , myelodysplasia 15 , myelofibrosis 16,17 , non-Hodgkins or Hodgkin lymphoma 1820 , and multiple myeloma 21,22 . In addition, a number of prospective studies have now been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The use of low-dose TBI in that report was associated with lower risk of engraftment failure 15 . A more recent study of 27 patients who received dUCB alloSCT for relapsed/refractory HL at two centers reported a 26% TRM at 100 days with two-year PFS and OS of 41% and 56%, respectively 16 . In this study, 5/11 dUCB transplants (45%) had relapsed/refractory HL.…”
Section: Discussionmentioning
confidence: 55%